Gambaran Pengetahuan Ibu Postpartum Tentang Perawatan Genetalia Pada Luka Perenium Di Rs Ahmad Muchtar Bukittinggi tahun 2014 - Ulsa Fitri, Yellyta; KhairannisaUmala Harahap, Darnisa (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Factors that favor infection genitalia tool many postpartum mothers in the community who do not pay attention to hygiene in the perineal wound her,through observation of 8 postpartum mothers with injuries perenium treated in inpatient Ahmad Muchtar Hospital Bukittinggi, there are 5 people who replace the pads postpartum maternal 1 a day and are afraid to clean his wounds perenium. While 3 postpartum mother who replace the pads at least 2-3 times a day and always cleans his wounds perenium. The research method is quantitative descriptive, research locations in the Ahmad Muchtar Hospital Bukittinggi in Oktober 2014 with the aim to find a picture of postpartum maternal knowledge about genitalia in the wound care perenium. Total population is taken in April 30 and respondents are taken entirely from the total population. Mechanical sampling Quota sampling technique. Data collection tool is a questionnaire with univariate analysis and frequency distribution table. Postpartum maternal knowledge about the understanding of the wound care genitalia perenium that for 29 respondents (97%) including high-level knowledge, knowledge about the implementation of genital care for 15 respondents (50%) including the medium category, the mother's knowledge about genitalia maintenance purposes by 27 (90%) and knowledge of mothers postpartum about genitalia in wound care perenium for 20 (67%). The results showed knowledge of postpartum mothers in the maternity hospital inpatient space Ahmad Muchtar Hospital majority have high knowledge, and can also be expected to maintain and take the few opportunities to remind mothers postpartum about genitalia in the wound care perenium.